Room temperature synthesis of ZIF-8 membranes from seeds anchored in gelatin films for gas separation1. Issue 7 (21st February 2015) - Hu, Pan; Yang, Yefeng; Mao, Yiyin; Li, Junwei; Cao, Wei; Ying, Yulong; Liu, Yu; Lei, Jiahuan; Peng, Xinsheng
<x xml:space="preserve">Abstract</x> ZIF-8 seeds anchored in gelatin films converted from zinc hydroxide nanostrands/gelatin composite films are desirable for secondary growth of well intergrown ZIF-8 membranes at room temperature, which demonstrate nice gas separation performance.